Polish Marxism after Luxemburg - Toporowski, Jan (Bingley, U.K. : Emerald Publishing Limited, 2022)
In this 37th issue of the Research in Political Economy series, Jan Toporowski and leading experts offer a unique and insightful overview of Polish Marxism after Luxemburg, serving as an introduction to some key themes and the ideas of several Polish political economists. Polish Marxism after Luxemburg covers various ideas that emerged around the same period as Rosa Luxemburg was active, such as Ludwik Krzywicki who pioneered the study of monopoly finance capital and suggested the possibility of industrial feudalism. Chapters illustrate the current relevance of these thinkers and highlight the development from Polish Marxism of Michal Kalecki and Oskar Lange, who went on to become one of the founders of what came to be called the Keynesian Revolution in macroeconomics and economic policy. After exploring the relationship of Kalecki to Marxism, through the work of Luxemburg. Polish Marxism after Luxemburg also illuminates a selection of Polish discussions in the political economy from the second half of the twentieth century, particularly in the circle of political economists around Oskar Lange, like Wlodzimierz Brus and Tadeusz Kowalik.
Introduction: Rosa luxemburg and Polish marxism / Jan Toporowski -- Chapter 1. Rosa luxemburg and say's law / Andrew Trigg -- Chapter 2. Henryk grossman's revolutionary marxism / Rick Kuhn -- Chapter 3. Industrial feudalism and American capitalism / Jan Toporowski -- Chapter 4. Industrial feudalism and the distribution of wealth / Hanna Szymborska and Jan Toporowski -- Chapter 5. Polish marxism: Kalecki / Peter Kriesler and Joseph Halevi -- Chapter 6. Rosa luxemburg and michal kalecki: A marxian view / Riccardo Bellofiore -- Chapter 7. Marxian and monetary aspects of kalecki / Jan Toporowski -- Chapter 8. Are kalecki's 'marxian reproduction schemes' really marxian? / Gabriele Pastrello -- Chapter 9. Between anti bureaucratism and technocratic democratization: Was oskar lange's socialist theory a tightrope walking? / Roberto Lampa -- Chapter 10. Wlodzimierz brus and the law of value under socialism / Jan Toporowski -- Chapter 11. Oskar lange and tadeusz kowalik on the bourgeois revolutions in twentieth-century Poland / Grzegorz Konat -- Chapter 12. Capitalism in crisis: Tadeusz kowalik on the birth and development of capitalism / Daniele Tori -- Chapter 13. False dawns: The failed crucial reforms of capitalism and socialism / Gavin Rae.
Includes bibliographical references and index.
Keywords: Socialism -- Poland -- History -- 20th century; Poland -- Politics and government -- 20th century; Business & Economics -- Economic History; Economic theory & philosophy